Paralemmin-1 controls the nanoarchitecture of the neuronal submembrane cytoskeleton - Macarrón Palacios, Victor; Hubrich, Jasmine; do Rego Barros Fernandes Lima, Maria Augusta; Metzendorf, Nicole; Kneilmann, Simon; Trapp, Marleen; Acuna Goycolea, Claudio; Patrizi, Annarita; D’Este, Elisa; Kilimann, Manfred (Science advances, 2025)
The submembrane cytoskeleton of neurons displays a highly ordered 190-nanometer periodic actin-spectrin lattice, the membrane-associated periodic skeleton (MPS). It is involved in mechanical resilience, signaling, and action potential transmission. Here, we identify paralemmin-1 (Palm1) as a component and regulator of the MPS. Palm1 binds to the amino-terminal region of βII-spectrin, and MINFLUX microscopy localizes it in close proximity (<20 nanometers) to the actin-capping protein and MPS component adducin. Combining overexpression, knockout, and rescue experiments, we observe that the expression level of Palm1 controls the degree of periodicity of the MPS and also affects the electrophysiological properties of neurons. A single amino acid mutation (W54A) in Palm1 abolishes the MPS binding and remodeling activities of Palm1. Our findings identify Palm1 as a protein specifically dedicated to organizing the MPS and will advance the understanding of the assembly and plasticity of the actin-spectrin submembrane skeleton in general.
Gesehen am 01.09.2025